Experiences of black women teacher educators in the South African higher education system: initiating debate - Maodzwa-Taruvinga, Mandivavarira; Divala, Joseph Jinja (South African Journal of Higher Education, 2016)
The documenting of Black women’s past and current experiences within academia remains important despite the apparent opening up of opportunities for the formerly excluded. This is due to the need to confront the twin edifices of domination and marginalisation arising from the legacies of colonialism and apartheid. Within the context of discourses on transformation, it is critical to take stock of the extent to which universities have created supportive and enabling environments that take account of the diverse and unequal backgrounds of their academics, especially women. This introductory paper serves to initiate aspects of the debates that inform the narratives of a group of Black women academics who are university-based teacher educators and to raise questions about their positioning within tertiary institutions which remain relevant even under a democratic and inclusive dispensation. Key words: Black women, academics, identity, narrative, teacher education, South Africa, university